Legal Protection of Processed “Nasi Kapau” Products are Linked to Intellectual Property Rights (Study at Nagari Kapau, Agam Regency) - Ulfanora Utama; Tasman (Journal of Law, Politic and Humanities, 2025)
West Sumatra is a province that has undoubted delicious cuisine that has gone global and is known as Minangkabau cuisine. One of the famous Minangkabau dishes is Nasi Kapau. Nasi Kapau is a traditional dish originating from Nagari Kapau and has special processed products that are different from dishes in the Minangkabau realm. In Law Number 20 of 2016 concerning Brands, the role of Brands and Geographical Indications is very important, especially in maintaining healthy, fair business competition, protecting consumers, as well as protecting Micro, Small and Medium Enterprises and domestic industry. In fact, there are already several Nasi Kapau dishes that have been registered with the Ministry of Law and Human Rights, such as Nasi Kapau Uni Lis.  The potential for not carrying out an inventory or recording it will give rise to legal problems, namely legal disputes. Various cases that have occurred bothclaim"The ownership of intellectual property by other people or other countries causes cultural losses and even loss of commercial value. The results of this research explain that First, Registration of the trademark on Nasi Kapau is an effort to avoid recognition by other countries which violates the ownership of the owner of the processed product. Second, Registration of the Kapau rice brand as a form of preservation carried out by the Nagari Kapau community for the advancement of Minangkabau culture in Indonesia. Third, The government encourages the public to register processed products in the form of kapau rice through individual brands and communal brands in the form of nasi Padang licenses. It is advisable for the people of Nagari Kapau to register their processed Kapau rice products in the form of a patent as a form of intellectual property rights protection in the form of appreciating their work for the sake of community welfare and a healthy business climate.